Analisis Pengaruh Sektor Pertanian dan Industri Pengolahan Terhadap Tingkat Kemiskinan di Kabupaten Kerinci - Tan, Rafnir; Delfia, Elka (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT - SEKOLAH TINGGI ILMU EKONOMI SAKTI ALAM KERINCI, 2018)
The purpose of this research is to know the Influence of Agricultural Sector and Processing Industry sector to Poverty in Kerinci Regency 2010-2014. Operational Variables in this study is the element of research that gives guidance as measured variables, while the variables referred to in this study are: Poverty Level (Variable Y), is a condition that is measured by comparing the number of population with the number of poor people in a certain year expressed in percent (%), Agricultural Sector (Variable X1), is the value of agricultural production which is donated to GRDP on the basis of current prices from 2010-2014 stated in rupiah, Manufacturing Processing Sector (Variable X2), is the value of industrial production processing in Kerinci Regency which is donated to GRDP over current prices from 2010-2014 stated in rupiah.